2023
DOI: 10.3390/ijms24043532
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Continuous Transcriptional Heterogeneity in High-Risk Blastemal-Type Wilms’ Tumors Using Unsupervised Machine Learning

Abstract: Wilms’ tumors are pediatric malignancies that are thought to arise from faulty kidney development. They contain a wide range of poorly differentiated cell states resembling various distorted developmental stages of the fetal kidney, and as a result, differ between patients in a continuous manner that is not well understood. Here, we used three computational approaches to characterize this continuous heterogeneity in high-risk blastemal-type Wilms’ tumors. Using Pareto task inference, we show that the tumors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
3
5
1
Order By: Relevance
“…Likewise, we observed that tumors located near the stromal archetype have a high proportion of cells resembling renal fibroblasts. We performed similar analysis on a dataset of high-risk blastemal-type Wilms' tumors (treated according to SIOP protocols) published by Wegert et al [14] and found similar results [20] (see a detailed comparison in the supplementary information).…”
Section: High-risk Wilms' Tumors and Normal Kidney Samples Form A Tri...supporting
confidence: 59%
See 2 more Smart Citations
“…Likewise, we observed that tumors located near the stromal archetype have a high proportion of cells resembling renal fibroblasts. We performed similar analysis on a dataset of high-risk blastemal-type Wilms' tumors (treated according to SIOP protocols) published by Wegert et al [14] and found similar results [20] (see a detailed comparison in the supplementary information).…”
Section: High-risk Wilms' Tumors and Normal Kidney Samples Form A Tri...supporting
confidence: 59%
“…We then performed sequence alignment and obtained a gene expression matrix (Table S1). Using Principal Components Analysis (PCA) we found that high-risk Wilms' tumors form a continuum in gene expression latent space rather 6 than discrete well-separated clusters [19,20] (Figure 1A-F). To better understand this continuous heterogeneity, we used Pareto Task Inference [36,38] to calculate the vertices of the best fitting polytope encompassing all tumors and normal kidney samples in latent space.…”
Section: High-risk Wilms' Tumors and Normal Kidney Samples Form A Tri...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [20], we observed that favorable histology Wilms' tumors (treated according to the COG protocol) form a triangular shaped continuum in gene expression latent space, and that the vertices of this triangle, which represent tumor "archetypes," have blastemal, stromal, and epithelial characteristics, corresponding to the three main lineages of the developing fetal kidney. In a consecutive study [21], we found that this geometry is also conserved in high-risk tumors that were treated with chemotherapy prior to surgery (according to the SIOP protocol) but still contained a significant amount of remaining viable blastema [15], and used a probabilistic generative model [22] to represent each tumor as a mixture of three latent biological "topics" with stromal, epithelial, and blastemal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We then performed sequence alignment and obtained a gene expression matrix (Table S1). Using Principal Component Analysis (PCA), we found that high-risk Wilms' tumors form a continuum in gene expression latent space rather than discrete well-separated clusters [20,21] (Figure 1A-F, Supplementary Figures S1-S6). To better understand this continuous heterogeneity, we used Pareto task inference [43,45] to calculate the vertices of the best fitting polytope encompassing all tumors and normal kidney samples in latent space.…”
Section: Introductionmentioning
confidence: 99%